Assessment of heavy metals bioconcentration factor (BCF) and genotoxicity response induced by metal mixture in Salmo salar tissues - Sauliutė, Gintarė; Stankevičiūtė, Milda; Svecevičius, Gintaras; Baršienė, Janina; Valskienė, Roberta (International Conference “Environmental Engineering”, 2017)
The aim of this study was to evaluate metals bioconcentration factor (BCF) in gills, liver, kidneys and muscle in relation with genotoxicity effects of metal mixture in peripheral blood, kidneys, gills and liver erythrocytes of the Atlantic salmon (Salmo salar). Fish were exposed to maximum ermissible waterborne concentrations of Zn – 0.1, Cu – 0.01, Ni – 0.01, Cr – 0.01, Pb – 0.005 and Cd – 0.005 mg/L, respectively for 7 and 14 days. Genotoxicity was studied using the micronucleus test. In addition, erythrocyte nuclear abnormalities (ENAs) were analysed. Our study indicates that metal BCF in Atlantic salmon is tissue-dependent. Based on the BCF classification scale, the relatively low values of metals bioconcentration were assessed, except for Zn (gills) and Cu (liver) (359.6 and 594.0, respectively). Zn intensively concentrated in fish tissues, while Pb – least of all. Overall, metals were concentrated mostly in the liver, least – in the muscle. Significant differences among BCF values of Pb in gills and muscle and Cd in gills were measured between 7 and 14 d exposure groups. Treatment with metal mixture significantly increased micronucleus frequencies after 7 d of exposure in liver and peripheral blood erythrocytes. Significant genotoxicity response was not observed after 14 d treatment. The erythrocytic nuclei abnormalities determined in S. salar blood were nuclear bud on filament (NBf), nuclear bud (NB), blebbed (BL), kidney shaped, vacuolated (VacNuc), 8-shaped nuclei and fragmented poptotic (FA) erythrocytes. Significant elevation in total ENAs level was detected in kidneys and liver erythrocytes after 7 d treatment, while after 14 d – in gills and kidneys erythrocytes. No significant differences among analysed responses were measured between 7 and 14 d exposure groups, except total ENAs level in liver erythrocytes.
Keywords: Salmo salar; metal mixture; bioconcentration factor (BCF); genotoxicity; nuclear abnormalities; micronuclei